2006
DOI: 10.17221/5020-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the developments in food safety systems formation in the world for dairy industry from the standpoint ofTurke

Abstract: Abstract:Food safety is important due to new protection measurements applied in the growing world trade as much as the raise and continuity of life quality. In recent years, the countries have begun to face with important problems both in domestic consumption and exportation, because of the sensitivity of consumers on the safety of food products. Regarding this, in the dairy industry, which is an important sub sector of the food industry, the food safety issues has begun to gain importance in developing countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It may also be due to poor conditions and infrastructure facilities in Aydın that are capable of analyzing only dry matter, acidity, and fat content. Similar findings are suggested by Demirbas et al (2006).…”
Section: Remarkssupporting
confidence: 89%
See 1 more Smart Citation
“…It may also be due to poor conditions and infrastructure facilities in Aydın that are capable of analyzing only dry matter, acidity, and fat content. Similar findings are suggested by Demirbas et al (2006).…”
Section: Remarkssupporting
confidence: 89%
“…According to new legislation, integration of the two sectors is essential for food safety in Turkey. There are many small plants that process a high number of dairy products (Demirbas & Karagozlu, 2008) but these same plants have demonstrated a lack of sufficient technical experience in food safety (Demirbas, Karahan, Kenanoglu, & Karagozlu, 2006). A lot of research exist characterizing food safety implementation in small and medium-sized food manufacturers (Celaya et al, 2007;Route, 2001;Violaris, Bridges, & Bridges, 2008;Walker, Pritchard, & Forsythe, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 7, our findings indicate that Turkish dairy plant manager's desire similar programming from the local agricultural organizations. Many studies have indicated that FSMS-related consultation services and training is a desired commodity in the Turkish food industry (Bas et al, 2007;Demirbas & Karagozlu, 2008;Demirbas et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During dairy processing, microorganisms from several sources e.g. personnel, water, equipment, additives and packaging materials (Demirbas, Karahan, Kenanoglu, & Karagozlu, 2006;Papademas & Bintsis, 2010) can contaminant the product. In addition, dairy products are also potential carriers of veterinary drugs, chemical pollutants and microbial toxins.…”
Section: Introductionmentioning
confidence: 99%
“…microorganisms from personnel, equipment and water, or even veterinary drugs, chemical pollutants and toxins can act as causative agents for many food-borne diseases [1,2]. The systematic approach to minimize economic losses and food poisoning outbreaks from all steps in the dairy production process has been positively affected by the development of the Hazard Analysis and Critical Control Point (HACCP) system and standards developed by the International Organization for Standardization (ISO), such as the ISO 9000 series [3].…”
Section: Introductionmentioning
confidence: 99%